2022
DOI: 10.1039/d2tc00432a
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in ZnIn2S4-based materials towards photocatalytic purification, solar fuel production and organic transformations

Abstract: Energy crisis and environmental purifications would be mitigated by photocatalytic technology, which could convert abundant and inexhaustible solar energy to chemical fuels as well as degrade detrimental pollutant to non-toxic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 200 publications
0
24
0
Order By: Relevance
“…To improve these issues, many strategies, such as doping modification, construction of heterojunctions, and the use of noble metal co-catalysts, have been developed. 7–9 In recent years, in addition to the methods above, a new type of photothermal catalysis reaction has emerged, and the introduction of thermal effects has greatly improved the efficiency of photocatalytic reactions. 10–12 Photothermal catalysis can combine the advantages of both photocatalysis and thermocatalysis, so that the utilization rate of solar energy is greatly improved, and excellent catalytic effects can be achieved even under ordinary reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…To improve these issues, many strategies, such as doping modification, construction of heterojunctions, and the use of noble metal co-catalysts, have been developed. 7–9 In recent years, in addition to the methods above, a new type of photothermal catalysis reaction has emerged, and the introduction of thermal effects has greatly improved the efficiency of photocatalytic reactions. 10–12 Photothermal catalysis can combine the advantages of both photocatalysis and thermocatalysis, so that the utilization rate of solar energy is greatly improved, and excellent catalytic effects can be achieved even under ordinary reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This is attractive for the fabrication of high‐performance photodetectors because the direct band gap endows the semiconductor to have a greater light absorption capability. [ 47 ] Subsequently, the XPS analysis was used to validate the surface elemental composition and the chemical state of the as‐prepared ZnIn 2 S 4 nanoflakes. The survey XPS spectrum (Figure S4 , Supporting Information) of the as‐prepared ZnIn 2 S 4 nanoflakes reveals the existence of Zn, In, and S elements, while the signals of C and O come from the atmospheric adsorbates.…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15] In recent years, the application of ZIS in the field of photocatalytic water splitting has been widely reported. [16][17][18] Guo et al prepared a ZnIn 2 S 4 @CuInS 2 core-shell p-n heterojunction (ZIS@CIS) using a two-step hydrothermal method. 19 The results showed that the CuInS 2 loading improved light absorption in the visible and near-infrared regions.…”
Section: Introductionmentioning
confidence: 99%